Development of Digital Flipbook Media to Improve Indonesian Language Learning Outcomes of Fourth Grade Students at State Elementary School Purwodadi 3 Malang - Khoirun Nisa; Ida Rinda Ningsih; Chosi Kasanda (Tinta Emas Publisher, 2025)
This study aims to develop, test the feasibility, and assess the effectiveness of digital flipbook learning media in improving the Indonesian language learning outcomes of fourth-grade students at Purwodadi 3 Elementary School, Malang. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of students of grades IV A and IV B and two Indonesian language teachers. Flipbook media was developed to facilitate vocabulary understanding, effective sentence construction, and simple paragraph writing through visual and interactive displays. The validation results showed that the media received a very feasible category from material experts and media experts. Teacher and student responses also showed a high level of interest and ease of use. Learning outcome data showed an increase in the average score from 67.4 to 86.1, with a percentage increase of 27.7%. These findings indicate that digital flipbook media is effective in improving the Indonesian language learning outcomes of fourth-grade students. Thus, digital flipbooks can be used as an alternative innovative learning media that supports active, interesting, and student-centered learning in elementary schools.